PROBLEMS OF BUSINESS ACTIVITY IN UKRAINE DURING MARITAL STATUS - MIAHKYKH, Iрина; DEMIANENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study of the problems of conducting business activities in the conditions of martial law is extremely relevant, since entrepreneurship itself plays a key role in the recovery of the economy of Ukraine. Studying these problems will allow not only to identify the main obstacles for business, but also to propose concrete solutions to overcome them, which is critical for the post-war recovery of the country.In the context of hostilities in Ukraine, there is a sharp decline in economic activity and a decrease in the effectiveness of entrepreneurial activity. Despite this, thanks to state support and international assistance, in particular from European countries, it was possible to partially restore and ensure the functioning of business entities even during the war. This allows businesses to adapt to new conditions and continue their operations in difficult circumstances. Support from the state was aimed at creating favorable conditions for doing business, which included reducing the tax burden, simplifying customs clearance and other measures. Financing of investment projects from foreign investors helped to support small and medium-sized businesses, which, in turn, made it possible to provide the population with jobs. The process of post-war reconstruction of the country and entrepreneurship will take place in several stages, depending on priorities. The key areas are the restoration of infrastructure in the de-occupied territories, the establishment of business ties, the reconstruction of housing and social facilities to ensure the return of the population. An important role in these processes is played by the resource potential of each specific territory after the end of hostilities. Today, the restoration of the economic and social component of the development of the regions and the country as a whole is an urgent task for the government, business and society.The purpose of the study is to identify and analyze the main problems of doing business in Ukraine during martial law, as well as to develop recommendations for supporting and restoring entrepreneurship in crisis situations, in particular in the war and post-war periods.Entrepreneurial activity is a key element of the functioning of the state, especially under martial law. During this period, existing problems have become more acute, in particular for micro, small and medium-sized businesses. Entrepreneurs face new challenges, such as disrupted supply chains, declining consumer demand, lost labor, and the need to adapt to uncertainty. In such conditions, the issue of ensuring stability and development of entrepreneurship becomes a priority for the state and society. The study of the problems of doing business in wartime allows not only to identify existing difficulties, but also to develop effective strategies to support enterprises, in particular, small and medium-sized enterprises, which are the basis of the Ukrainian economy. In the context of the ongoing martial law in Ukraine, entrepreneurial activity has faced unprecedented challenges and difficulties. Martial law has led to significant changes in the economic environment that have affected all aspects of business, from production to the supply of goods and services.To maintain the viability of entrepreneurship under martial law, it is necessary to implement effective strategies that include state support, international assistance, search for new markets and adaptation to the changed economic situation. Post-war reconstruction remains an important aspect, which requires comprehensive approaches to the restoration of infrastructure, production facilities and business ties. The problems of doing business in Ukraine during martial law have significantly complicated the conditions for business functioning. The main challenges were the destruction of logistics chains, a decrease in the purchasing power of the population, loss of access to financial resources, labor migration and regulatory changes. Despite these difficulties, enterprises continue to adapt thanks to government support, the help of international partners, and the search for new markets.The decisive factor for economic recovery after the war will be a comprehensive approach to rebuilding infrastructure, supporting businesses and attracting investment. Only through the joint efforts of the state, business and the international community can it be possible to ensure the stable development of entrepreneurial activity in Ukraine in the conditions of the war and post-war period.
Keywords: Entrepreneurship; post-war reconstruction; development; martial law; problems